Nitric oxide derived from endothelial cells inhibits Na+/H+ exchange in rabbit platelets activated by thrombin - Chen Hua; Guo Zhao-gui (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of nitric oxide (NO) derived from endothelial cells on Na+/H+ exchange in rabbit platelets activated by thrombin. METHODS: Intracellular Ca2+ ([Ca2+]i) and intracellular pH (pHi) were measured by the dual-wavelength fluorophotometer with the fluorescent probes Fura-2 and 2',7'-biscarboxyethyl-5,6-carboxyfluorescein (BCECF). Effects of NO on rabbit platelets were tested by cultured bovine endothelial cells (BAEC). RESULTS: BAEC (0.1-1 x 10(9).L-1) inhibited thrombin (100 U.L-1)-induced platelet aggregation in a concentration-dependent manner. This inhibiting effect was abolished by preincubating BAEC with NG-nitro-L-arginine 1 mmol.L-1. When the [Ca2+]i store was depleted with ionomycin in the presence of egtazic acid (EGTA), the increase in pHi induced by thrombin was inhibited. Refilling intracellular Ca2+ store partially reversed this effect. BAEC 2 x 10(8).L-1 inhibited thrombin (100 U.L-1)-induced elevation of pHi and mobilization of intracellular Ca2+ store (P < 0.01). No direct effect of endothelial cells on unstimulated rabbit platelets was observed. CONCLUSION: NO derived from endothelial cells inhibited thrombin-induced rabbit platelet activation by inhibiting thrombin-induced [Ca2+]i mobilization and then inhibiting the consequent Na+/H+ exchange in rabbit platelets.